The effects of oil price shocks on U.S. stock order flow imbalances and stock returns - Lambertides, Neophytos; Savva, Christos S.; Tsouknidis, Dimitris (My University, 2017)
This paper investigates for the first time the effects of oil demand shocks and oil supply shocks on stock order flow imbalances leading to changes in stock returns. Through the estimation of a structural VAR model, positive oil demand shocks are able to explain almost 36% of the observed variation in the daily average stock order flow imbalances measured by the buy/sell trades ratio; which consequently lead to a negative rather than positive stock returns reaction. In contrast, oil supply shocks exhibit a negative and marginally significant effect on stock order flow imbalances. Our aggregate analysis suggests that positive shocks on stock order flow imbalances are negatively related to stock returns. These effects are stronger for oil-related sectors when compared with the rest of the equities sectors.
Keywords: Oil price shocks; Stock order flow imbalances; Structural VAR